Pengolahan Buah Salak Pada Jemaat Desa Haunatas dalam Meningkatkan Ekonomi Umat di Tengah Realitas Kemiskinan - Gusti Dametriana Sihombing (International Forum of Researchers and Lecturers, 2024)
Salak is a fruit that can be harvested throughout the year, it can also benefit farmers, especially in Haunatas village in Marancar sub-district, South Tapanuli district. Through the processing of salak, it can increase the economy of the people there, especially congregations who experience poverty in the economy. In an effort to improve the community's economy, several governments have made things or efforts to reduce this poverty and also the church has a very important role in this matter where the Church provide some knowledge in the form of knowledge skills and also donations in the form of funds for knowledge in processing salak fruit. Salak fruit can be processed into various preparations, such as making snake fruit dodol, snake fruit jam and other sweets. With this processing, it can reduce some of the poverty in the congregation, although not everything can be coordinated well. However, at least the church has tried to overcome poverty in the congregation, especially in the village of Haunatas, by utilizing snake fruit which is a characteristic of that area.